If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x-5=x-5
We move all terms to the left:
-x-5-(x-5)=0
We add all the numbers together, and all the variables
-1x-(x-5)-5=0
We get rid of parentheses
-1x-x+5-5=0
We add all the numbers together, and all the variables
-2x=0
x=0/-2
x=0
| 7-3r=1-4(2+r) | | 5(x+4)+2x=4(x-5)+11x | | .10(y-6)+0.02y=0.08y-0.07(10) | | y=-6.7 | | 15x+34=4.5x+64 | | x-6÷2=x-4 | | -7-7m=-7(m+1) | | n-25.5=-44.8 | | 9(3y+3)=15(3y-9)+24 | | 13-0.5(8d+12)=-5d-14 | | 3-(3x-2)=12 | | -m/2=34 | | 125+5z=250 | | 3a=a+40 | | -2(n-1)-1=-5-4n | | x+7=10+ | | -2/3v=13 | | 5x+7=4x+10(73.55 | | 5y=108 | | 1.2=y+2.7 | | |x|-8=1 | | 10y-(-3)=4y+63 | | -15+7.5(2d-1)=7+5 | | .4x+1.7=3.3 | | 2t=t+10 | | 7n+7-12n=5n+6-9n | | 1/7y+3=-8 | | 4+5q=7 | | 176=4t | | -5(1-5n)=2n-5 | | 5/3x+2/9=3 | | 4/5x=1100 |